Molecular cloning and expression of Macrobrachium rosenbergii L-type lectin in Escherichia coli / Chan Chew Chin - Chan , Chew Chin (2019)
Macrobrachium rosenbergii, also known as the giant freshwater prawn represents a valuable commodity in aquaculture farming all over the world. The lack of adaptive immunity system in M. rosenbergii renders difficulty in development of effective treatment for both pathogenic viral and bacterial infections. Existing disease control relies on effective biosecurity measures such as pathogen-free larvae stock and meticulous cultivation environment management. The effort to elucidate innate defence responses towards pathogens’ invasion provides valuable insights for better disease prevention and control. Lectins are recognised as a crucial component in pattern recognition receptor (PRR), facilitating phagocytosis and pathogen clearance from infected hosts. Recently, attention has been placed on L-type lectins regarding on their potential involvement in innate immune response. This project has cloned and expressed the L-type lectin domain protein, MrLTL, characterised from M. rosenbergii. This protein comprises a signal peptide, L-type lectin domain, a transmembrane region, with a total sequence length of 323 amino acids. Two major carbohydrate-binding motifs, YSN and GDL, were identified. The predictive structure of the protein adopts a beta-sandwich fold solved via homology modelling. Bioinformatics simulation demonstrates preferential binding of mannose-type ligands towards MrLTL with extensive hydrogen bond formation. The production of soluble MrLTL will provide insights into structure and function of this protein, which in turn serve as an effort to expand the current knowledge on L-type lectin in crustacean species.